Receptor-binding domain-anchored peptides block binding of severe acute respiratory syndrome coronavirus 2 spike proteins with cell surface angiotensin-converting enzyme 2 - Wang, Ting; Xu, Jie; Wang, Beibei; Wang, Yulian; Zhao, Wei; Xiang, Bin; Xue, Yuhua; Yuan, Quan; Wang, Yiqiang (Frontiers in Microbiology, 2022)
Background: COVID-19 pandemic has killed over six million people worldwide. Despite the accumulation of knowledge about the causative pathogen SARS-CoV-2 and the pathogenesis of this disease, cures remain to be discovered. We searched for certain peptides that might interfere with spike protein-ACE2 interactions. Methods: Phage display-12 peptide library was screened against recombinant spike trimer (S-trimer) or receptor-binding domain (S-RBD) proteins. The resulting enriched peptide sequences were obtained, and their potential binding sites on S-trimer and S-RBD 3D structure models were searched. Synthetic peptides corresponding to these and other reference sequences were tested for their efficacy in blocking the binding of S-trimer protein onto recombinant ACE2 proteins or ACE2-overexpressing cells. Results: After three rounds of phage selections, two peptide sequences (C2, DHAQRYGAGHSG; C6, HWKAVNWLKPWT) were enriched by S-RBD, but only C2 was present in S-trimer selected phages. When the 3D structures of static monomeric S-RBD (6M17) and S-trimer (6ZGE, 6ZGG, 7CAI, 7CAK, each with different status of S-RBDs in the three monomer spike proteins) were scanned for potential binding sites of C2 and C6 peptides, C6 opt to bind the saddle of S-RBD in both 6M17 and erected S-RBD in S-trimers, but C2 failed to cluster there in the S-trimers. In the competitive S-trimer-ACE2 binding experiments, synthetic C2 and C6 peptides inhibited S-trimer binding onto 293T-ACE2hR cells at high concentrations (50 μM) but not at lower concentrations (10 μM and below), neither for the settings of S-trimer binding onto recombinant ACE2 proteins. Conclusion: Using phage display methodology, two peptides were generated bearing potentials to interfere with spike protein-ACE2 interaction, which might be further exploited to produce peptidomimetics that block the attachment of SARS-CoV-2 virus onto host cells, hence diminishing the pathogenesis of COVID-19.